Metabolic engineering of the C16 homoterpene TMTT in Lotus japonicus through overexpression of (E, E)‐geranyllinalool synthase attracts generalist and specialist predators in different manners. Issue 4 (19th August 2013) - Brillada, Carla; Nishihara, Masahiro; Shimoda, Takeshi; Garms, Stefan; Boland, Wilhelm; Maffei, Massimo E.; Arimura, Gen‐ichiro
Summary: Plant defenses against herbivores include the emission of specific blends of volatiles, which enable plants to attract natural enemies of herbivores. We characterized a plastidial terpene synthase gene, PlTPS2, from lima bean ( Phaseolus lunatus ). The recombinant PlTPS2 protein was multifunctional, producing linalool, ( E )‐nerolidol and ( E, E )‐geranyllinalool, precursors of ( E, E )‐4, 8, 12‐trimethyltrideca‐1, 3, 7, 11‐tetraene [TMTT]. Transgenic Lotus japonicus and Nicotiana tabacum plants, expressing PlTPS2 or its homolog Medicago truncatula TPS3 ( MtTPS3 ), were produced and used for bioassays with herbivorous and predatory mites. Transgenic L. japonicus plants expressing PlTPS2 produced ( E, E )‐geranyllinalool and TMTT, whereas wild‐type plants and transgenic plants expressing MtTPS3 did not. Transgenic N. tabacum expressing PlTPS2 produced ( E, E )‐geranyllinalool but not TMTT. Moreover, in olfactory assays, the generalist predatory mite Neoseiulus californicus but not the specialist Phytoseiulus persimilis was attracted to uninfested, transgenic L. japonicus plants expressing PlTPS2 over wild‐type plants. The specialist P. persimilis was more strongly attracted by the transgenic plants infested with spider mites than by infested wild‐type plants. Predator responses to transgenic plant volatile TMTT depend on various background volatiles endogenously produced by the transgenic plants. Therefore, the manipulation of TMTT is an ideal platform for pest control via the attraction of generalist and specialist predators in different manners.